Socioeconomic and environmental status of riverside communities of Tapajós River, Brazil. (30th September 2020) - Rodrigues, J; Leite, B; Vasconcellos, G; Dias, L A; Muniz, M J; Espinosa, M V; Nishida, N; Ferrero, M V; Reis, B; Cabral, E R
Abstract: Introduction: Public health care acknowledges socioeconomic factors as one of the multiple facets to promote or protect individual or collective health. Understanding and being more acquainted with the dynamics carried out in riverside communities is fundamental to investing in policies aimed at fighting diseases and illnesses that are particular to those communities. Objective: Describing socioeconomic characteristics, healthcare infrastructure, and occupational activities of population from riverside communities along Tapajós river, Brazil. Methodology: A descriptive study with 96 residents of communities of Tapajós river, Brazil. Participants have answered a semi-structure questionnaire and the analyses were descriptive and the variable categories were expressed as frequencies. Results: There was a predominance of male participants (77.09%), incomplete elementary school (58.51%), involved in agricultural sector (85.10%), with a family income up to 1 minimum wage (68.81%). However, only 21.50% have declared making their living exclusively out of agriculture. Seedlings and seeds are mainly obtained through an exchange system running inside the community. In relation to infrastructure, the water comes from artesian wells (68.88%) and 51.63% claim not treating water whatsoever. All interviewees mentioned the lack of a sewage system and residues are taken to a rudimentary cesspool (76.59%). Waste produced by the community is burned out (93.61%). The main difficulties pointed out by the interviewees were: transportation (44.94%), health (32.14%), communication (21.42%) and government cooperation (15.47%). Conclusions: The communities in this project show similar structural dynamic based on subsistence family agriculture and poor infrastructure of basic services. The data collected can be the basis for future public policies aiming at the promotion of food production autonomy, economic autonomy, and improvement of health indicators of these communities. Key messages: Contextualizing the structural dynamic of vulnerable populations is key to plan actions aimed at tackling and dealing with social determinants involved in the health-illness process. Contextualizing the structural dynamic of vulnerable populations is fundamental to guide strategies aimed at intervening in the social and health determinants.